AB0907 Neck Pain Makes No Odds on Cervical Alignment in Patients with Temporomandibular Disorders. (15th July 2016) - Coskun Benlidayi, I.; Guzel, R.; Tatli, U.; Salimov, F.; Keceli, O.
Abstract : Background: Despite the extensive research on the possible link between cervical posture and temporomandibular disorders (TMDs), it still remains as a highly controversial issue. The inconclusive results derived from the previous studies, might be in part due to the ignorance of neck pain, which usually accompanies TMDs. Objectives: In the present study, we aimed to elucidate the impact of neck pain-if any-on cervical alignment in patients with TMDs. Methods: °Patients diagnosed with TMDs according to the research diagnostic criteria for TMDs (RDC/TMD) between November 2013-November 2015 were included in the study. All subjects underwent lateral cervical x-ray evaluation and were asked to complete the RDC/TMD Axis II Biobehavioral Questionnaire for TMDs. Pain, disability and depression scores for TMD were calculated. Computerized measurement of the cervical lordosis angle was performed according to the C2-C7 cobb method. Additionally, disability score for neck pain was measured through Neck Disability Index (NDI) in patients with concomitant neck pain. The study sample was divided into two groups according to the presence of neck pain and a comparative analysis for cervical lordosis angle was carried out between groups. The relation of cervical malalignment with neck disability, TMD-associated pain, depression and disability was evaluated via Pearson's correlation analysis. Results: The study sample was consisted of 60 patients with a mean age of 31.2±10.8 years. The mean value for cervical lordosis angle in the whole group was 10.9±12.7°, which was consistent with hypolordosis. Cervical lordosis angle did not differ between patients with (n=28) and without (n=32) neck pain (12.2±12.8° versus 9.8±12.7°, respectively; p=0.46). Cervical alignment was correlated with neither neck disability nor TMD-related variables including pain intensity, depression and disability. Conclusions: Patients with TMDs have hypolordotic cervical malalignment regardless of neck pain. The presence of neck pain makes no odds on patients' cervical alignment. Disclosure of Interest: None declared